PENINGKATAN MINAT BACA SISWA SEKOLAH DASAR MELALUI CLASSROOM READING PROGRAM - Zahida, Najla; Mawaddah, Ismatul; Khairani, Syifa; Harvia Rizky, Nabila; Safitri Syam, Salmaini; Suriani, Ari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading interest is one of the fundamental competencies that must be developed in elementary school students as a foundation for lifelong learning. However, the reading interest of Indonesian elementary school students remains low, as reflected in various international literacy surveys. This study aims to analyze the effectiveness of the Classroom Reading Program (CRP) in improving reading interest among elementary school students. The method used is a literature review with a descriptive qualitative approach, analyzing various national and international journal sources. The findings show that CRP, implemented through structured reading activities, reading aloud, peer reading, and reading journals, can significantly increase students' reading motivation and habits. This program also creates a supportive literacy environment in the classroom, builds positive reading culture, and strengthens teacher-student interaction around books. The study concludes that Classroom Reading Program is an effective, sustainable, and replicable strategy for improving elementary school students' reading interest when supported by teachers' commitment and parental involvement.